The Politics of Language in Constructing Civil Identity: Case of Bosnia and Herzegovina - T. I. Popadeva (Vestnik MGIMO-Universiteta)
Civil identity is one of the most significant factors in modern political practice. Today’s identity formation and development of large national groups is less based on a cultural and historical foundation and increasingly depends on political technologies. Among them, the construction of new languages plays an important role. The article studies the Bosnian language policy, which, contrary to forming a common civil identity, as a result of the politicization of linguistic norms becomes a factor in creating a “forge of hatred”. Drawing on constructivist social theories, the author summarizes Bosnian linguistic practices and examines them through the prism of symbolic interactionism and negative feedback systems. Particular attention is paid to situations when the desire for effective communication motivates speakers to abandon ethnically colored linguistic markers and situations in which the language acts as a defense against the internal “other.” Applying the criteria for distinguishing between language and dialects, the author concludes that the phonetic principle of the Serbo-Croatian language formation made it possible, after the destruction of Yugoslavia, to turn this linguistic continuum into an identification weapon to delimit the citizens of one country. This experience helps analyze the politicization of literary interpretations and linguistic norms in other regions of the world, where there are also examples of the growth of xenophobia, nationalism, and intolerance resulting from a differentiating language policy.